Impact of Mobile Assisted Language Learning (MALL) on EFL: A Meta-Analysis - Taj, Imtiaz Hassan; Norrihan, Sulan; Sipra, Muhammad Aslam; Ahmad, Waqar (Australian International Academic Centre, Australia, 2016)
Mobile Assisted Language Learning (MALL) has emerged as a potential tool in the instruction of English as a foreign language (EFL). Meta-analysis of 13 studies published between year 2008 and 2015 was conducted. Four point criteria for the selection of studies for analysis is based on the year of publication, quasi-experimental design, pretest and posttest method and finally use of mobile device for intervention. Findings of the analysis suggest that MALL has fostered the EFL instruction. Overall effect size was (d = 0.8) which is considered a large effect size.